Factors Influencing Critical Thinking: Problem Base Learning, Discovery Learning, and Project Base Learning - Bagus H, Bambang; Bambang Suprianto; Arie Wardhono; Cris Kuntadi (Dinasti Publisher, 2023)
This paper aims to determine the improvement of critical thinking. The development of critical thinking skills can be done through the intervention of learning models. In a study or scientific publication, previous or pertinent research is crucial. The theory and phenomena of linkages or influences between variables are strengthened by prior research or pertinent research in this regard. This article examines learning paradigms such as problem-based learning, discovery learning, and project-based learning as well as other elements that affect critical thinking. Building a hypothesis of influence between variables for use in future studies is the goal of this article. The result of this literature review article is 1) problem base learning affects critical thinking; 2) discovery learning affects critical thinking; and 3) project base learning affects critical thinking.